Distribution, prevalence and intensity of moose nose bot fly (Cephenemyia ulrichii) larvae in moose (Alces alces) from Norway - Rolandsen, Christer M.; Madslien, Knut; Ytrehus, Bjørnar; Hamnes, Inger Sofie; Solberg, Erling J.; Mysterud, Atle; Vikøren, Turid; Våge, Jørn; Hanssen, Oddvar; Miller, Andrea L. (Zenodo, 2021)
Rolandsen, Christer M., Madslien, Knut, Ytrehus, Bjørnar, Hamnes, Inger Sofie, Solberg, Erling J., Mysterud, Atle, Vikøren, Turid, Våge, Jørn, Hanssen, Oddvar, Miller, Andrea L. (2021): Distribution, prevalence and intensity of moose nose bot fly (Cephenemyia ulrichii) larvae in moose (Alces alces) from Norway. International Journal for Parasitology: Parasites and Wildlife 15: 120-126, DOI:10.1016/j.ijppaw.2021.04.012, URL: http://dx.doi.org/10.1016/j.ijppaw.2021.04.012